Gerenciamento dinâmico de buffers em players de vídeo IPTV para melhoria do QoE - Mendes , Marcos Paulo; Moreno, Marcelo Ferreira (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2016: Anais Estendidos do XXII Simpósio Brasileiro de Sistemas Multimídia e Web, 2016)
Due to recent technological evolution, the provision of IPTV services has grown considerably. One of the services normally included in IPTV is Linear TV, where audiovisual contents are made available in the form of program schedules. In this context, challenges emerge regarding the distribution of multimedia content over this serevice. One of these challenges is speciﬁcally the user’s perception about the quality of the IPTV service, measured in terms of quality of experience (QoE). Thus, this article aims to analyze the problems that may occur when receiving content and to propose solutions to these problems. Speciﬁcally, due to the congestion of transmission media or overload in the endpoints, a key issue is the statistical variation of time delay for multimedia content delivery (packet jitter). This paper’s proposal comprises a dynamic management of buﬀers in IPTV terminal devices, taking into account the individual characteristics of Linear TV service, thereby improving the quality of user experience.